Firework and sparkler burns in paediatric patients - Daniel Ricciardello; Nam Kyu Yang; Kira Chamberlain; Andrew Holland (Australasian Journal of Plastic Surgery)
**Background**: While the consumer sale of fireworks is illegal in New South Wales, the sale of sparklers is legal—however, both still pose a significant risk of harm in the paediatric population. Anecdotally, burns services are aware that the misuse of sparklers can result in burns but there appears to be a paucity of studies examining this incidence in the paediatric population in Australia.